Some peculiarities of mechanical properties of amorphous metal alloys - Abramov, V.S.; Beloshov, O.N.; Prokofieva, O.V. (Functional Materials, 2004)
First experimental results are presented on amorphous Fe₈₀B₂₀ alloy strip spontaneous straining demonstrating itself as the strip twisting and simultaneous change in the sampl e length under linear heating. The coherent phenomena are simulated mathematically, the model applicability to description of relaxation processes in amorphous metal alloys has been checked. Приводятся первые экспериментальные результаты для ленты аморфного сплава Fe₈₀B₂₀ по обнаружению спонтанной деформации, проявляющейся в виде кручения ленты и одновременного изменения длины образца в процессе линейного нагрева. Выполнено математическое моделирование когерентных явлений, опробована их применимость для описания релаксационных процессов в аморфных металлических сплавах. Подано перші експершментальні результати для стрічки аморфного сплаву Fe₈₀B₂₀ з виявлення спонтанної деформації, що виявляється як крутіння стрічки та одночасна зміна довжини зразка в процесі лінійного нагрівання. Виконано математичне моделювання когерентних явищ, випробувано їх придатність для опису релаксаційних процесів в аморфних металевих сплавах.